“We Feel Like We’re Home”: The Resettlement and Integration of Syrian Refugees in Smaller and Rural Canadian Communities - Haugen, Stacey (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2019)
Despite the media attention to Syrian refugee families being welcomed, finding work, and feeling at home in small towns across Canada, little is known about resettlement and integration in smaller and rural communities. Addressing this knowledge gap, this study visited four rural communities across four provinces in an effort to highlight the experiences of smaller and rural communities and the refugees living there. Based on interviews and conversations with rural refugee sponsors and community members, Syrian refugees, and service providers, the findings tell a story of refugees being welcomed into rural and smaller communities and of communities coming together to support the newcomers and find solutions to rural challenges. The article concludes that rural places can have a lot to offer refugees, some of whom settle permanently in these areas, and their experiences should be included as part of the larger narrative of refugee resettlement in Canada.